Study of bacterial susceptibility to antibiotic and phage combinations: a literature review - Olga E. Punchenko; Vladimir V. Gostev; Elizaveta V. Punchenko; Marina V. Savchenko (Журнал микробиологии, эпидемиологии и иммунобиологии)
The aim of the review is to describe existing laboratory methods for determining the sensitivity of bacteria to a combination of antibiotics and bacteriophages. However, more and more often there are scientific papers in which their combined action is described as synergism. The mechanisms of this phenomenon have not been fully studied, but it has been proven that not only virulent but also moderate phages can enter into synergy with antibiotics, allowing the minimum inhibitory concentration of the antibiotic to be reduced several times. Since synergy cannot yet be empirically predicted, microbiological laboratories use various in vitro methods, most of which are labor-intensive. The development of a new technique that can be introduced into the daily practice of microbiological laboratories is relevant.